A new bronchoscopic catheter for the transbronchial ablation of pulmonary nodules - Safi, Seyer; Winkel, Jan op den; Muley, Thomas; Herth, Felix (Lung cancer, 2018)
Objectives - With the objective of simultaneous bronchoscopic biopsy and ablation of malignant solitary pulmonary nodules, we have developed a flexible monopolar radiofrequency (RF) catheter that can be deployed through the working channel of most bronchoscopes. - Materials and Methods - Fresh tumor specimens were heated in a water bath to 37 °C, and the RF catheter was inserted into the tumors within the specimen. Temperature sensors were positioned 3 mm, 5 mm and 7 mm from the electrode to measure the temperature of the surrounding tissue every 1 s. The ablation was conducted by applying RF energy for 8 min. The ablated specimens were evaluated by cutting the tissue samples along the top of the device and measuring the ablation zones. - Results - Five ablations were performed in 3 specimens. All of the ablation zones had a major axis length (along the electrode axis) between 18.9 mm and 22.8 mm and a minor axis length (perpendicular to the major axis) between 13.3 mm and 18.0 mm. The temperature data showed that all of the temperature sensors detected 60 °C or higher. These results demonstrate that the RF catheter was capable of generating ablation zones that were locally contained in ex vivo human cancerous lung specimens and that incorporated the tumor tissues. - Conclusion - We present the results of a benchtop study demonstrating the local control of ablation achieved using the RF device. This study suggests that the ex vivo ablation of lung malignancy with a new bronchoscopic RF catheter is feasible and that in vivo tumor ablation with this method in humans merits further study.
Gesehen am 14.05.2019